DPP6 localization in brain supports function as a Kv4 channel associated protein - Clark, Brian D.; Kwon, Elaine; Maffie, Jon; Jeong, Hyo-Young; Nadal, Marcela; Strop, Pavel; Rudy, Bernardo (Frontiers in Molecular Neuroscience, 2008)
The gene encoding the dipeptidyl-like protein DPP6 (also known as DPPX) has been associated with human neural disease. However, until recently no function had been found for this protein. It has been proposed that DPP6 is an auxiliary subunit of neuronal Kv4 K+ channels, the ion channels responsible for the somato-dendritic A-type K+ current, an ionic current with crucial roles in the regulation of firing frequency, dendritic integration and synaptic plasticity. This view has been supported mainly by studies showing that DPP6 is necessary to generate channels with biophysical properties resembling the native channels in some neurons. However, independent evidence that DPP6 is a component of neuronal Kv4 channels in the brain, and whether this protein has other functions in the CNS is still lacking. We generated antibodies to DPP6 proteins to compare their distribution in brain with that of the Kv4 pore-forming subunits. DPP6 proteins were prominently expressed in neuronal populations expressing Kv4.2 proteins and both types of protein were enriched in the dendrites of these cells, strongly supporting the hypothesis that DPP6 is an associated protein of Kv4 channels in brain neurons. The observed similarity in the cellular and subcellular patterns of expression of both proteins suggests that this is the main function of DPP6 in brain. However, we also found that DPP6 antibodies intensely labeled the hippocampal mossy fiber axons, which lack Kv4 proteins, suggesting that DPP6 proteins may have additional, Kv4-unrelated functions.